2000
DOI: 10.4049/jimmunol.165.6.2932
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Functional Requirement for SAP in 2B4-Mediated Activation of Human Natural Killer Cells as Revealed by the X-Linked Lymphoproliferative Syndrome

Abstract: X-linked lymphoproliferative syndrome (XLP) is an immunodeficiency characterized by life-threatening infectious mononucleosis and EBV-induced B cell lymphoma. The gene mutated in XLP encodes SLAM (signaling lymphocytic activation molecule-associated protein)-associated protein (SAP), a small SH2 domain-containing protein. SAP associates with 2B4 and SLAM, activating receptors expressed by NK and T cells, and prevents recruitment of SH2 domain-containing protein tyrosine phosphatase-2 SHP-2) to the cytoplasmic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
185
0
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(198 citation statements)
references
References 33 publications
10
185
0
1
Order By: Relevance
“…These studies suggested a “lack of function” of 2B4 31 32. Further studies should clarify these divergent results and in particular whether they reflect a heterogeneity of the patients phenotype or other yet unknown mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies suggested a “lack of function” of 2B4 31 32. Further studies should clarify these divergent results and in particular whether they reflect a heterogeneity of the patients phenotype or other yet unknown mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…A dramatically altered function of 2B4 has recently been detected in individuals affected by the X-linked lymphoproliferative disease (XLP [28, 31, 32]). XLP is a severe inherited immune deficiency, characterized by the inability to control EBV infection resulting in fulminant infectious mononucleosis or lymphoma 33 34.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in NK cells derived from these patients both CD244 and NTBA have been shown transduce abnormal inhibitory signals resulting in sharp inhibition of cytotoxicity against EBV-infected cells [1,[19][20][21]. This may contribute to the pathogenesis and to the progression of the disease since B-EBV-infected cells are characterized by high levels of expression of CD244-and NTBA-specific ligands, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in the absence of SH2D1A molecule, the interaction of CD244 and NTBA with their ligands on EBVinfected cells has been shown to transduce inhibitory signals that render XLP-NK cells unable to kill EBVinfected targets [19][20][21]. While the ligand recognized by CD244, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The important role of 2B4 has been implicated in various infection and clinical settings. For example, a number of studies revealed that an inability to signal via 2B4 due to a genetic defect in SAP may contribute to the pathogenesis of XLP [25][26][27]. Human 2B4 expression is up-regulated on CD8 + T lymphocytes raised in response to herpes simplex virus (HSV), which lysed infected cells more efficiently [28].…”
Section: Introductionmentioning
confidence: 99%